2002
DOI: 10.1353/dem.2002.0028
|View full text |Cite
|
Sign up to set email alerts
|

Mortality rates of elderly Asian American populations based on medicare and social security data

Abstract: We present sex- and age-specific death probabilities for the elderly of six Asian American subgroups--Chinese, Filipino, Indian, Japanese, Korean, and Vietnamese--based on data from social Security Administration files. We determined ethnicity by combining race, place of birth, surname, and given name. The data source and ethnic determination are the same for deaths and the population at risk, avoiding the problem of noncomparability present when data for the numerator come from vital records and data for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 6 publications
3
31
1
Order By: Relevance
“…These findings are also surprising when contrasted with findings regarding mortality among other ethnic minority groups in the US, such as Hispanic-Americans [36], [37] and Asian-Americans [38] that have demonstrated advantages in life expectancy and all-cause mortality relative to Whites.…”
Section: Discussioncontrasting
confidence: 61%
“…These findings are also surprising when contrasted with findings regarding mortality among other ethnic minority groups in the US, such as Hispanic-Americans [36], [37] and Asian-Americans [38] that have demonstrated advantages in life expectancy and all-cause mortality relative to Whites.…”
Section: Discussioncontrasting
confidence: 61%
“…Elo et al (2004) found lower mortality at ages 65+ during the period 1980–1989 among Hispanics born in Cuba, Mexico, and selected other foreign countries than among U.S.-born Hispanics. Lauderdale and Kestenbaum (2002) found lower mortality in the 1990s among six Asian subgroups (Chinese, Indian, Japanese, Korean, Filipino, Vietnamese) than among non-Hispanic whites.…”
Section: Discussionmentioning
confidence: 86%
“…The Numident file is a record of all applications and re-applications for a Social Security number and card, and provides information on country of birth and dates of Social Security card applications. The Medicare data linked to Social Security records have been used in several studies to estimate mortality at older ages in the United States (Dupre et al 2012; Elo et al 2004; Kestenbaum and Ferguson 2002; Lauderdale and Kestenbaum 2002; Preston et al 1996; Turra and Elo 2008). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations